Penerapan Graph Theory and Matrix Approach Sebagai Pendukung Keputusan Pemilihan Varietas Unggul Kedelai - Lazulfa, Indana; Mufarrihah, Iftitaahul; Andriani, Anita; Widoyoningrum, Sri Widoyoningrum; Firdaus, Reza Augusta Jannatul (Progresif: Jurnal Ilmiah Komputer, 2024)
Soybean is a very important commodity in Indonesia because it usually used as the main daily meal protein source for the Indonesian people. Soybean has various varieties originating from within and outside the country. According to BPS data, soybean consumption increases by around 0.15 million tons per year. Meanwhile, in 2016, the amount of domestic soybean demand exceeded the amount of domestic soybean production, so the government imported it from outside the country. Even though there are 85 data on superior varieties released by Balitkabi, this does not guarantee that soybean production will increase. The decline in soybean production is also related to the constraints of agricultural land in Indonesia which is being massively transformed into residential land or other areas due to the fairly high population growth rate. This research aims to optimize soybean production through accurate selection of superior superb varieties. The method used in this research is a multicriteria decision making method, namely graph theory and matrix approach (GTMA). The results obtained were the 46 best varieties from 85 datasets based on certain criteria. The accuracy of GTMA shows an average of 86.95%. These results show that GTMA is a multi-criteria method that is feasible to implement.Keywords: Soybean; Multicriteria; Graph theory and matrix approach; Decision makingÂ  Â AbstrakKedelai merupakan komoditas yang sangat penting di Indonesia karena biasa dimanfaatkan sebagai sumber protein utama harian penduduk Indonesia. Kedelai memiliki beragam varietas yang berasal dari dalam dan luar negeri. Menurut data BPS, konsumsi kedelai meningkat sekitar 0.15 juta ton per tahun. Sedangkan pada tahun 2016, jumlah kebutuhan kedelai dalam negeri melebihi jumlah produksi kedelai dalam negeri sehingga pemerintah melakukan impor. Meskipun ada 85 data varietas unggul yang dirilis oleh Balitkabi tetapi hal tersebut tidak menjamin bahwa produksi kedelai meningkat. Penurunan prooduksi juga berkaitan dengan kendala lahan pertanian di Indonesia yang secara massif bertransformasi menjadi lahan pemukiman atau lainnya karena laju pertumbuhan penduduk yang cukup tinggi. Penelitian ini bertujuan untuk mengoptimalkan produksi kedelai melalui ketepatan pemilihan varietas unggul. Metode yang digunakan dalam penelitian ini merupakan metode pengambilan keputusan multikriteria yakni graph theory and matrix approach (GTMA). Hasil yang diperoleh adalah 46 varietas terbaik dari 85 dataset berdasarkan kriteria tertentu. Akurasi dari GTMA menunjukkan rata-rata sebesar 86.95%. Dari hasil tersebut menunjukkan bahwa GTMA merupakan metode multikriteria yang layak untuk diimplementasikan.Kata kunci: Kedelai; Multikriteria; Graph theory and matrix approach; Pendukung keputusanÂ